Sequencing and analysis of the complete mitochondrial genome of Gymnogobius laevis. Issue 5 (4th May 2022) - Peng, Lina; Li, Peilun; Li, Hui; Zhao, Wenyan; Wang, Hongkun; Li, Zheng; Sun, Lili
Abstract: Gymnogobius laevis (Steindachner, 1879) is a small, benthic freshwater fish. In a previous study, it was reported as a rare resident in Heilongjiang Province. In this study, the mitochondrial genome of G. laevis was sequenced. It is 16, 519 base pairs (bp) in length and contains 13 protein-coding genes, two ribosomal RNA genes (12S rRNA and 16S rRNA), 22 transfer RNA genes (tRNA), and two non-coding control regions. The A + T content is 55.71% in the G. laevis mitochondrial genome. A phylogenetic tree shows that G. laevis is closely related to the family Gobiinae based on complete mitogenome sequences.